Intensitätsstufen des Bewässerungsfeldbaus im Peshawar-Becken, Pakistan: Besonderheiten der Zuckerproduktion im konkurrierenden Anbaugebiet von Zuckerrohr und Zuckerrübe - Andreae, Bernd (ERDKUNDE, 1984)
Predominantly part of the sub-tropical arid belt of the old world and a densely settled developing country, Pakistan has already put 71.5% of its cultivated area under irrigation. An extraordinarily productive irrigation agriculture has developed in the Peshawar Basin at the foot of the Khyber Pass (Hindu Kush) especially. The warm climate, together with the rivers which carry water all the year round, easily enable two crops a year to be grown unless perennial or permanent crops limit the crop sequence. Particularly interesting developments have been observed in the technical advances in the cultivation of winter sugar-beet, which has now become one of the most productive and most lucrative branches of soil utilization in the Peshawar Basin. Here it has entered an area formerly under cultivation with sugar-cane, albeit without ousting the cane. On the contrary, both the sugar-producing plants of the global economy hold their own and are in competition not only in the sense of political economy but also of business economics. This applies to the production of raw materials in industry. Crop sequences have been developed which include both these cultivars, and sugar factories which alternately process both these raw materials. Nowhere in the world has there been a comparable extent and comparable success carrying such conviction in the competition between sugar-cane and sugar-beet both at the level of production and in the partnership at the processing stage.